Polymer-Lipid Hybrid Nanoparticles: A Next-Generation Nanocarrier for Targeted Treatment of Solid Tumors - Rizwanullah, Md.; Alam, Meraj; Harshita; Mir, Showkat R.; Rizvi, Mohd. M.A.; Amin, Saima (Current Pharmaceutical Design, 2020)
At present, cancer is the most deadly disease and one of the most common causes of death worldwide providing different obstacles to chemotherapy including non-specific biodistribution of chemotherapeutic drugs, dose-related adverse effects, development of metastasis and chemoresistance. Nanoparticle-based targeted delivery of chemotherapeutics gained enormous attention in the treatment of solid tumors as they provide many significant advantages including prolonged drug release, enhanced systemic half-life, decreased toxicity and targeted drug delivery. Polymer–lipid hybrid nanoparticles (PLHNPs) are the most effective nanoplatform that develop from building blocks of polymers and lipids. PLHNPs combine the unique advantages of both lipid-based nanoparticles as well as polymeric nanoparticles. PLHNPs integrate biocompatible polymers and biomimetic lipids in their architecture, which imparts PLHNPs with wide versatility for delivering chemotherapeutic drugs of different physicochemical characteristics to their target site of action. The hybrid architecture of PLHNPs provides many exceptional advantages such as small particle size, encapsulation of more than one anticancer drugs, high drug loading capacity and modified drug release profile. Furthermore, the surface decoration of PLHNPs improves the therapeutic potential of the chemotherapeutic drug by selective targeting of tumor tissue and reduces the side effects by decreasing non-specific biodistribution. This review highlights the challenges in the treatment of solid tumors by using nanoparticles system, rationale and targeting strategies of PLHNPs in the targeted treatment of solid tumors, and current progress of PLHNPs in the management of different types of solid tumors.
Keywords: cellular uptake